2013
DOI: 10.1371/journal.pone.0071393
|View full text |Cite|
|
Sign up to set email alerts
|

Endogenous Retrovirus EAV-HP Linked to Blue Egg Phenotype in Mapuche Fowl

Abstract: Oocyan or blue/green eggshell colour is an autosomal dominant trait found in native chickens (Mapuche fowl) of Chile and in some of their descendants in European and North American modern breeds. We report here the identification of an endogenous avian retroviral (EAV-HP) insertion in oocyan Mapuche fowl and European breeds. Sequencing data reveals 100% retroviral identity between the Mapuche and European insertions. Quantitative real-time PCR analysis of European oocyan chicken indicates over-expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 46 publications
5
52
2
3
Order By: Relevance
“…In the event that two breakpoints were observed within an interval, they were found either to be 6 bp apart, corresponding to the size of a target-site duplication and so might be attributed to soft-clipped reads from the LTR at either end of the virus (chr2:129,140,825–129,141,707 and chr3:84,550,518–84,551,452; S9), or the integration was present in the reference genome and the breakpoints corresponded closely with the LTR alignment (chr1:182,715,565–183,138,508; S10). This is in contrast to that which has been recently observed at the oocyan locus for Chinese and South American chicken populations [ 8 , 9 ].…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In the event that two breakpoints were observed within an interval, they were found either to be 6 bp apart, corresponding to the size of a target-site duplication and so might be attributed to soft-clipped reads from the LTR at either end of the virus (chr2:129,140,825–129,141,707 and chr3:84,550,518–84,551,452; S9), or the integration was present in the reference genome and the breakpoints corresponded closely with the LTR alignment (chr1:182,715,565–183,138,508; S10). This is in contrast to that which has been recently observed at the oocyan locus for Chinese and South American chicken populations [ 8 , 9 ].…”
Section: Resultscontrasting
confidence: 99%
“…Desfarges and Ciuffi [ 6 ] indicate that alpharetroviruses display a weak preference for integration in transcription units of genes and CpG islands, which are enriched in gene-rich regions. This is consistent with the EAV-HP integration sites identified for the oocyan phenotype in chicken [ 8 , 9 ], which integrates into the promoter region of SLCO1B3 . Bolisetty et al [ 7 ] report a near random distribution of ERV integration sites, although this may be an artefact of the preferences of different retrovirus genera.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…All the variation in the coloration of birds' eggshells is thus far known to be the product of just two ancient and highly conserved [ 17 ], tetrapyrrole pigments: biliverdin IXα, and protoporphyrin IX [ 18 – 21 ]. While the genetic and biochemical mechanisms by which colorful eggshell pigments are formed are not yet fully understood [ 22 ], the prevailing consensus is that protoporphyrin, a cyclic tetrapyrrole which produces red-brown maculation [ 23 ], is an immediate precursor of the heme molecule, whereas biliverdin, a linear tetrapyrrole which gives the eggshell a blue-green hue, is a byproduct of hemoglobin breakdown [ 18 20 , 24 ]. The basic biochemistry of avian eggshell pigments has received considerable attention [ 17 , 19 – 21 ] and subsequently, the presence or absence of protoporphyrin and biliverdin in eggshells has been documented for several extinct moa species [ 17 ] and more than 100 species of extant birds [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent research found that ChERV plays an important role in both qualitative and quantitative traits as follows. ChERVs have been found to be involved in blue eggshell [9,10], recessive white [11], late feathering [12] and henny feathering phenotype [13]. In addition, the effects of ChERVs on exogenous avian tumor viruses infection including leukosis virus (ALV), reticuloendotheliosis viruses (REV) and Marek's disease virus (MDV) have also been documented [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%